Introduction of an ex-vivo pig model for teaching percutaneous nephrolithotomy access techniques - Forbes, Connor M.; Lim, Jonathan; Chan, Justin; Paterson, Ryan F.; Gupta, Mantu; Chew, Ben H.; Scotland, Kymora (Canadian Urological Association Journal, 2018)
Introduction: In North America, obtaining access for percutaneous nephrolithotomy (PCNL) is not often performed by urologists. Hands-on training sessions help to ensure this skill continues within the urological community. An ex-vivo pig kidney model was developed for simulation. This model uses porcine tissues with a fluoroscopic C-arm and standard PCNL equipment. The bullseye or triangulation techniques are both possible. We propose this as a high-fidelity tool for teaching PCNL access. Methods: The pig kidney, fat, ribs, flank, and skin were arranged anatomically on a table with fluoroscopy. Hands-on training was provided to residents and urologists using the ex-vivo pig model and a silicone-based percutaneous access model. Questionnaires were given at the end of the session. Results: There was a total 14 responders for each model, with incomplete responses on two surveys. A total of 15% of responders for the pig model and 7% of responders for the silicone model had previous percutaneous access experience. For the pig model, 93% of trainees agreed or strongly agreed that the model was easy to use, and 79% of the silicone model trainees felt the same. After the session, 50% of silicone model trainees and 86% of pig model trainees reported increased confidence in their ability to obtain PCNL access. All the pig model trainees and 71% of the silicone model trainees felt that the simulation activity was worthwhile. Conclusions: The inexpensive but anatomically realistic ex-vivo pig model using real-world equipment provides trainees with an excellent tool to learn PCNL access.